Early diagenesis of iron and sulfur in Bornholm Basin sediments: The role of near-surface pyrite formation. (1st September 2020) - Liu, Jiarui; Pellerin, André; Antler, Gilad; Kasten, Sabine; Findlay, Alyssa J.; Dohrmann, Ingrid; Røy, Hans; Turchyn, Alexandra V.; Jørgensen, Bo Barker
Abstract: Pyrite formation in marine sedimentary environments plays a key role in the global biogeochemical cycles of carbon, sulfur and iron, regulating Earth's surface redox balance over geological time scales. The sulfur isotopic composition of pyrite is one of the major geochemical tools for investigating early diagenetic processes in modern marine sediments and substantive changes to the Earth's surface environment in ancient sedimentary rocks. We studied sulfur–iron diagenesis and the sulfur isotopic evolution in sediments of the Bornholm Basin, southwestern Baltic Sea, to track the formation of pyrite in the near-surface sediments. Pyrite accumulation is observed with depth over the uppermost 100 cm before the extent of pyritization of the highly reactive iron pool (Fepy /FeHR ) stays constant at ca. 0.9, suggesting that the use of a single iron-speciation parameter as a proxy for anoxic and sulfidic conditions needs to be supported by other independent indicators in sedimentary records. Stable sulfur isotopic analysis demonstrates that the bulk pools of elemental sulfur and iron monosulfide do not exchange isotopes completely with aqueous sulfide. We suggest that the reactions with polysulfide and aqueous sulfide are probably restricted to the surface of the solid-phase sulfur and iron-sulfur aggregates. Although pyrite is growing throughout the uppermost sediment column, the pyrite at depth has a sulfur isotopic composition similar to that of pyrite formed near the sediment surface. To understand the isotopic discrepancy between pyrite and aqueous sulfide in the deeper sediments, we developed a simple diagenetic model, which reproduces the observed sulfur isotopic composition of pyrite well. Our results suggest that much of the pyrite is rapidly formed near the sediment–water interface, and its δ 34 S is not as influenced by the 34 S-enriched pool of aqueous sulfide in the deeper part of the sediment, allowing 32 S-enriched pyrite to be preserved in deeper sediments. This near-surface diagenesis and the associated isotopic pattern are possibly of relevance for many marine sediments with high organic matter content, and high aqueous sulfide but low reactive iron availability. Moreover, our sulfur isotopic data demonstrate that extremely slow pyritization is ongoing in the deep lacustrine clay sediments. These results have implications for the interpretation of sulfur–iron geochemical data in both modern and ancient settings as well as for improving reconstructions of ancient depositional environments and a better understanding of the marine sulfur cycle throughout Earth's history.